MYC and AMPK–Save Energy or Die! - Haikala, Heidi M.; Anttila, Johanna M.; Klefström, Juha (Frontiers in Cell and Developmental Biology, 2017)
MYC sustains non-stop proliferation by altering metabolic machinery to support growth of cell mass. As part of the metabolic transformation MYC promotes lipid, nucleotide and protein synthesis by hijacking citric acid cycle to serve biosynthetic processes, which simultaneously exhausts ATP production. This leads to the activation of cellular energy sensing protein, AMP-activated protein kinase (AMPK). Cells with normal growth control can stop cell proliferation machinery to replenish ATP reservoirs whereas MYC prevents such break by blocking the cell cycle exit. The relentless cell cycle activation, accompanied by sustained metabolic stress and AMPK activity, switches the energy-saving AMPK to pro-apoptotic AMPK. The AMPK-involving metabolic side of MYC apoptosis may provide novel avenues for therapeutic development. Here we first review the role of anabolic MYC and catabolic AMPK pathways in context of cancer and then discuss how the concomitant activity of both pathways in tumor cells may result in targetable synthetic lethal vulnerabilities.